Infected Lymphocele Extending to the Leg after Robot-Assisted Radical Prostatectomy and Pelvic Lymph Node Dissection - Jung, Hyun Jin (Urogenital tract infection, 2017)
Lymphocele infection is a rare complication after radical prostatectomy and pelvic lymph node dissection (PLND). Here, we present a case of lymphocele infection that extended to the leg two months after robot-assisted laparoscopic radical prostatectomy and PLND. The patient was a 60-year-old man whose chief complaints were fever, chills, and right thigh pain. Computed tomography showed infected lymphocele with right thigh abscess. After percutaneous drainage and intravenous antibiotics, the infection and right thigh abscess were resolved. KCI Citation Count: 0